Earnings management and corporate governance: Portuguese unlisted firms - Paiva, I.; Dias, P.; Palma, M. (2020 15th Iberian Conference on Information Systems and Technologies (CISTI), 2020)
The main objective of the investigation is to verify the existence of a correlation between the management of results and the following characteristics related to corporate governance: The size of the management composition; the number of external control entities, the audit performed by one of the four largest consultants and the percentage of women on corporate boards. The empirical study was based on unlisted companies in Portugal, with a total of 50.505 corporations and between 2008 and 2016. To conclude, corporate governance is a process system that follows the financial, economic and organizational nature and it characterizes how companies are managed and controlled. For this reason, the results of this study allow us to conclude that the policies and values of corporate governance have an impact on the financial performance and financial reporting of companies.